Efektifitas Arang Batok Kelapa dalam Menurunkan Kadar Nikel, E Coli, dan Kekeruhan pada Air Sumur Gali - Idayani Sangadjisowohy; Sumiati Tomia; Jasman Jasman; Risman S. Duka (Poltekkes Kemenkes Padang, 2025)
Water is essential for human life, as it plays a crucial role in various biological processes within the body, with water constituting 50-70% of total body weight. This study aimed to assess the effectiveness of coconut shell charcoal in reducing levels of nickel, E. coli, and turbidity in dug well water. An experimental research design with a